The Pathology of IgG4-Related Disease in the Bile Duct and Pancreas - Zen, Yoh (Seminars in Liver Disease, 2016)
Immunoglobulin G4-related disease (IgG4-RD) in the pancreatobiliary system manifests as sclerosing cholangitis (SC), hepatic inflammatory pseudotumors, and type 1 autoimmune pancreatitis (AIP). The pathology of IgG4-RD involves an inflammatory process and fibrogenic pathway, the combination of which damages the affected organs. Fibroinflammatory injury is characterized by three microscopic findings: a diffuse lymphoplasmacytic infiltrate rich in IgG4-positive plasma cells, obliterative phlebitis, and storiform fibrosis. Although the diagnosis of IgG4-related pancreatocholangitis is relatively straightforward in surgical specimens, the current clinical requirement is to diagnose patients using biopsy samples, which remains challenging. Histological differential diagnoses include primary SC, follicular cholangitis/pancreatitis, SC with granulocytic epithelial lesions, and type 2 AIP. Although the massive infiltration of IgG4-positive plasma cells is a histological hallmark of IgG4-RD, many other immune cells (e.g., Th2 lymphocytes, regulatory T cells, and M2 macrophages) appear to be strongly involved in orchestral immune reactions.
Keywords: immunoglobulin G4; sclerosing cholangitis; autoimmune pancreatitis